2013
DOI: 10.1088/0957-4484/24/31/315502
|View full text |Cite
|
Sign up to set email alerts
|

High performance stretchable UV sensor arrays of SnO2 nanowires

Abstract: A high performance, stretchable UV sensor array was fabricated based on an active matrix (AM) device that combined field effect transistors of SWCNTs and SnO2 nanowires. The AM devices provided spatial UV sensing via the individual sensors in the array. SnO2 NW UV sensors showed an average photosensitivity of ∼10(5) and a photoconductive gain of ∼10(6) under very low UV (λ = 254 nm) power intensities of 0.02-0.04 mW cm(-2). The UV sensing performance was not deteriorated by a prestrain of up to 23% induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…6(c). The value of the exponent (0.9 instead of 1.0) is attributed to the current loss arising from the recombination of e-h pairs [53][54].…”
mentioning
confidence: 99%
“…6(c). The value of the exponent (0.9 instead of 1.0) is attributed to the current loss arising from the recombination of e-h pairs [53][54].…”
mentioning
confidence: 99%
“…In general, tin particles or SnO 2 /C mixed powders are selected as precursor for the synthesis of SnO 2 nanowires . Alternatively, we have used elemental tin as a precursor in our study and have investigated the effect of the growth parameters and Au layer thickness on the synthesized nanostructures.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies include transfer printing of an island-bridge device matrix onto a pre-strained elastomer, 79 using wavy topography, 152 or producing an island-bridge configuration with stretchable serpentine interconnects. 154 Because of their direct bandgap in the UV region and a high sensitivity to UV illumination, 1D inorganic nanostructures (e.g., ZnO NWs, 148 SnO 2 NWs, 155 and Zn 2 SnO 4 NWs 147 ) have been used to produce stretchable UV PDs. Stemming from their large surface-to-volume ratio, the 1D nanostructure has many surface traps that can prolong the lifetime of the photocarrier; 156 furthermore, the large aspect ratio enables mechanical resilience to bending and stretching.…”
Section: A Light Sensorsmentioning
confidence: 99%
“…157 In 2013, Kim et al reported a stretchable UV sensor produced by transferring SnO 2 NW field effect transistors (FETs) onto a radially stretched disk-shaped PDMS substrate. 155 The subsequent elastic recovery of the PDMS caused the released Au/Ti/PI substrate to exhibit a buckled structure due to compressive strain.…”
Section: A Light Sensorsmentioning
confidence: 99%